2019
DOI: 10.1007/s00005-019-00553-6
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Chronic Subclinical Systemic Inflammation in Sprague–Dawley Rats Stimulated by Intermittent Bolus Injection of Lipopolysaccharide

Abstract: Induction of chronic subclinical systemic inflammation in sprague-dawley rats stimulated by intermittent bolus injection of lipopolysaccharide ABSTRACT Chronic subclinical systemic inflammation has a key role in stimulating several chronic conditions associated with cardiovascular diseases, cancer, rheumatoid arthritis, diabetes, and neurodegenerative diseases. Hence, developing in vivo models of chronic subclinical systemic inflammation are essential to the study of the pathophysiology and to measure the immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 53 publications
1
12
2
2
Order By: Relevance
“…Consistently, two experimental endotoxemia models have suggested that in humans, intravenous administration of endotoxin can increase peripheral neutrophils and plasma cytokines (Grigoleit et al, 2010;Taudorf et al, 2007). In addition, during intraperitoneal intermittent LPS injection, pro-inflammatory mediators including C-reactive protein, TNF-α, IL-1β, IL-6, and IL-8, as well as peripheral neutrophils, monocytes, and lymphocytes, were elevated in rats, indicating chronic subclinical systemic inflammation (Ranneh et al, 2019). However, the above changes of neutrophils and monocytes were shown in the endotoxemia or systemic inflammation models, whereas the participants in this study were healthy children.…”
Section: Discussionmentioning
confidence: 60%
“…Consistently, two experimental endotoxemia models have suggested that in humans, intravenous administration of endotoxin can increase peripheral neutrophils and plasma cytokines (Grigoleit et al, 2010;Taudorf et al, 2007). In addition, during intraperitoneal intermittent LPS injection, pro-inflammatory mediators including C-reactive protein, TNF-α, IL-1β, IL-6, and IL-8, as well as peripheral neutrophils, monocytes, and lymphocytes, were elevated in rats, indicating chronic subclinical systemic inflammation (Ranneh et al, 2019). However, the above changes of neutrophils and monocytes were shown in the endotoxemia or systemic inflammation models, whereas the participants in this study were healthy children.…”
Section: Discussionmentioning
confidence: 60%
“…Известно, что хроническое воспаление отражается увеличением лейкоцитов в периферической крови, в первую очередь нейтрофилов и моноцитов. Увеличивается также и соотношение нейтрофилов к лимфоцитам [1,7]. При ревматоидном артрите эндотелиоциты и клетки синовиальной оболочки поврежденных суставов экспрессируют медиаторы воспаления, такие как IL-1, IL-2, TNF-α и др.…”
Section: оригинальные исследованияunclassified
“…В группе без лечения данный индекс также был низок, однако за счет значительного повышения уровня сегментоядерных нейтрофилов. Такая картина характерна для истощенного иммунитета, в результате чего высок риск вторичных бактериальных осложнений [7]. Лимфоцитарный индекс оказался пониженным в группах без лечения, c АСОН ORN2 и преднизолоном (начиная с 14-х су-Рис.…”
Section: оригинальные исследованияunclassified
“…Additionally, besides the need for a deeper understanding of chronic inflammation, there is a strong need to target accurate animal models that reflect the biochemical and metabolic manifestations of the homeostatic disruption, which is generated by chronic inflammation. In this sense, a variety of studies have developed models to mimic acute or chronic inflammation using chemical or biological stimuli [ 13 , 14 ]. However, the isolation of chronic inflammation is challenging because it appears concomitantly with other conditions, and it does not exist separately in humans.…”
Section: Introductionmentioning
confidence: 99%
“…However, the isolation of chronic inflammation is challenging because it appears concomitantly with other conditions, and it does not exist separately in humans. Experimentally, one of the preferred stimuli for inducing chronic inflammation is the administration of lipopolysaccharide (LPS), a structure found in the outer membrane of gram-negative bacteria, which could be injected either intravenously or intraperitoneally, with different doses and frequency [ 14 , 15 , 16 , 17 ]. Furthermore, adjustment of administration, dose and frequency, together with additional approaches, allowed the development of different models of chronic inflammation diseases (e.g., CVDs or NAFLD) [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%